Inhibition of indoleamine 2, 3‐dioxygenase 1 expression alters immune response in colon tumor microenvironment in mice. Issue 8 (14th July 2015) - Takamatsu, Manabu; Hirata, Akihiro; Ohtaki, Hirofumi; Hoshi, Masato; Ando, Tatsuya; Ito, Hiroyasu; Hatano, Yuichiro; Tomita, Hiroyuki; Kuno, Toshiya; Saito, Kuniaki; Seishima, Mitsuru; Hara, Akira
<x xml:space="preserve">Abstract</x> Indoleamine 2, 3‐dioxygenase (IDO), an enzyme that degrades the essential amino acid l‐tryptophan along the kynurenine pathway, exerts immunomodulatory effects in a number of diseases. IDO expression is increased in tumor tissue and in draining lymph nodes; this increase is thought to play a role in tumor evasion by suppressing the immune response. A competitive inhibitor of IDO is currently being tested in clinical trials for the treatment of relapsed or refractory solid tumors, but the efficacy of IDO inhibition in colorectal tumors remains to be fully elucidated. In this study, we investigated the effect of IDO deficiency on colon tumorigenesis in mice by genetic deletion and pharmacological inhibition. Ido1‐deficient(−/−) mice were crossed with ApcMin/+ mice or were administered azoxymethane with or without dextran sodium sulfate. Ido1 deficiency did not lead to significant differences in the size and number of colon tumors. Similarly, the pharmacological inhibition of IDO using 1‐methyltryptophan (1‐mT) also resulted in no significant differences in tumor size and number in ApcMin/+ mice. However, Ido1 deficiency altered the immune response in the tumor microenvironment, showing a significant increase in mRNA expression of pro‐inflammatory cytokines and a significant decrease in the number of Foxp3‐positive regulatory T cells in the colon tumors of Ido1(−/−) mice. Importantly, 1‐mT treatment also significantly altered cytokine expression in the colon tumor tissues. These results suggest that IDO inhibition alone cannot sufficiently suppress colon cancer development in mice despite its immunomodulatory activity in the tumor microenvironment.